Inuit pride becomes an annual tradition - Wright, Trevor (APTN News, 2023)
Inuit pride parades became a new tradition since 2021 and LGBTQ+ people say it's made a huge improvement in feeling accepted.
Canada
Keywords: 2023-06 June; LGBTQ+